A Study of Teachers’ Perceptions of Challenges in Employing Child-Centered Approach in Selected State Primary Schools in Keng Tung Area, Myanmar - Aung, Aein Aein; Ye, Yan (Scholar: Human Sciences, 2015)
This study tried to identify the level of perceptions of teachers towards challenges in employing child-centered approach in their schools and to compare the differences in their perceptions according to their demographics. This research was conducted on a total population of 51 teachers in eight state primary schools in Kengtung area, Eastern Shan State, Myanmar. The research was designed as quantitative research by using a set of questionnaire which covers teachers’ demographic profiles including teachers’ age, educational background, years of teaching experience and grade level. Ten challenges of teachers based on previous research and related literatures were provided in questionnaire to identify the level of teachers’ perceptions towards challenges. The collected data were analyzed by using descriptive statistics, frequency and percentage, mean and standard deviation, One-Way Analysis of Variance (ANOVA). In addition to survey questionnaire, the researcher did observation and informal interview to some teachers. The study found out that most of the given challenges were perceived not challenging by the teachers in selected state primary schools in Kengtung area of Myanmar. Nevertheless, the findings of the research revealed new challenges for teachers such as language barrier, parents’ involvements, time insufficiency and learning ability of students. There were no significant differences in teachers’ perceptions of challenges in employing child-centered approach according to their age, educational background, years of teaching experience and grade level.